2003
DOI: 10.3349/ymj.2003.44.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Toxoplasma gondiiAntibodies in Haemodialysis Patients with Chronic Renal Failure

Abstract: One hundred and seventy three haemodialysis patients, and 40 healthy controls, were studied for the prevalence of anti-Toxoplasma gondii antibodies by a micro enzyme-linked immunosorbent assay (ELISA). Anti-T. gondii IgG antibodies were detected in 97 (56.06%) haemodialysis patients and 8 (20%) controls with a statistical significance. In addition, anti-T. gondii IgM antibodies were detected in 1.73% of patients, but none of the controls. In conclusion, a high percentage of positivity for Toxoplasma antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
5
7
6
2
Order By: Relevance
“…This result is the same as that of Ocak et al (17) who studied hemodialysis patients and healthy volunteers in Turkey. On the other hand, Aufy et al (21), Sahinl et al (16), Maraghi et al (18), Ebrahim Zadeh et al (19) , Rezavand et al (20) and Nissaptorn et al (23) studies determined 16.7%, 6.8% , 8.6 %, 13.5%, 3.3% and 5.7% respectively in the patient groups, which is not compatible with our results.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…This result is the same as that of Ocak et al (17) who studied hemodialysis patients and healthy volunteers in Turkey. On the other hand, Aufy et al (21), Sahinl et al (16), Maraghi et al (18), Ebrahim Zadeh et al (19) , Rezavand et al (20) and Nissaptorn et al (23) studies determined 16.7%, 6.8% , 8.6 %, 13.5%, 3.3% and 5.7% respectively in the patient groups, which is not compatible with our results.…”
Section: Discussioncontrasting
confidence: 90%
“…The results of the patient group share a similar frequency with figures reported in Turkey (76.5%) (17). However, the data in our study were higher than those reported by Sahinl et al (16) (59.1%) and Maraghi et al (18), Ebrahim Zadeh et al (19) and Rezavand et al (20) of 59.1% ,40.67% , 56.7% and 60%, respectively in Iran, and Aufy et al (21) and Alvarado-Esquivel et al (22) of 56.06%, 56.7% and 10%, respectively in Turkey, Egypt and Mexico; whereas in our results the percentage of Anti-Toxoplasma gondii IgG antibody in the volunteer group was more than other studies (17-22). Furthermore, in our study, there were no positive cases of anti- Toxoplasma gondii IgM antibody in the patient group and only 2.76% of the healthy volunteer showed the IgM antibody.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations